2006
DOI: 10.1086/508748
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blind, Placebo‐Controlled Efficacy Trial of a Bivalent Recombinant Glycoprotein 120 HIV‐1 Vaccine among Injection Drug Users in Bangkok, Thailand

Abstract: Despite the successful completion of this efficacy trial, the vaccine did not prevent HIV-1 infection or delay HIV-1 disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
640
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 749 publications
(654 citation statements)
references
References 37 publications
8
640
1
5
Order By: Relevance
“…Indeed, we found that gp120 sulfation in certain continuous cell lines is inefficient, presumably because of limited endogenous expression of tyrosyl sulfotransferases. This observation has important practical implications, because cell lines such as CHO and HEK293 are widely used for the production of recombinant gp120 for structural, biological, and clinical studies, including atomic-level structure determination (6-10, 18), standardized neutralization assays (46), and experimental vaccine trials (47,48). These considerations emphasize the need to use in vitro expression systems that implement physiologically relevant posttranslational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that gp120 sulfation in certain continuous cell lines is inefficient, presumably because of limited endogenous expression of tyrosyl sulfotransferases. This observation has important practical implications, because cell lines such as CHO and HEK293 are widely used for the production of recombinant gp120 for structural, biological, and clinical studies, including atomic-level structure determination (6-10, 18), standardized neutralization assays (46), and experimental vaccine trials (47,48). These considerations emphasize the need to use in vitro expression systems that implement physiologically relevant posttranslational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…(C) Subunit rotation along designated subunit axes (S 1 , S 2 , and S 3 , as previously described, protruding out of the plane of the page) further weakens gp120/gp41 interface, likely freeing up gp41 N-helix for association with the C-helix. ment of gp140 in a metastable state and the putative locations of its exposed epitopes contribute to the characterization of subsequent events occurring prior to membrane fusion, and utilization of gp140 as an immunogen in the unliganded and liganded forms with knowledge of epitope location and exposure could prove useful in elicitation of antibodies against both conserved epitopes, as opposed to the use of monomeric gp120 or of adenovirus-based cell-mediated immunity, thus providing a feasible direction for rational immunogen design (12,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Education, identification and treatment of infected persons with antiretroviral drugs, male circumcision, condoms, and needle exchange programs have been effective at curtailing the epidemic, but declines in the rate of new infections have plateaued, and it appears unlikely that the goal of <500 000 new adult infections per year will be achieved by 2020. An effective HIV‐1 vaccine could contribute to further reductions of infections as part of a coordinated prevention strategy,2 but to date, testing of candidate vaccines in efficacy trials has been disappointing 3, 4, 5, 6, 7 with only one trial showing any degree of vaccine efficacy 8…”
Section: Introductionmentioning
confidence: 99%